Empowerment of Local Government Officials in Managing Waste to Support Sustainable Development (Case Study in Lebak Regency) - Fadjarenie, Agustin; Nugroho, Lucky; Utami, Wiwik; Mappayunki, Ratna; Daito, Apollo; Oktris, Lin; Andesto, Ronny; Yusoff, Yusliza Mohd; Muhammad, Zikri; Rosufila, Zuha (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
The circular economy emerged as a response to the aspiration to realize sustainable development in anticipation of production and consumption pressures on natural resources and the environment. In this economic system concept, waste management is carried out optimally, where the result of recycling waste will be a value-added product while reducing waste residue. The objectives of the community service program are to provide solutions to waste management problems in Lebak Regency, provide alternative business development using appropriate technology so that there is an increase in the economy of the community in Lebak Regency, and at the same time, build disciplined behavior in maintaining the environment. This service method uses Participatory Action Research (PAR), which involves community members as co-researchers in identifying educational needs, developing strategies, and implementing solutions. Furthermore, the method used was through the delivery of socialization to participants in a hybrid manner. The socialization material includes (i) the importance of waste processing, (ii) how to sort waste, and (iii) economic added value from waste processing. The results of community service are in the form of solving problems the community faces by utilizing the expertise of relevant academicians related to waste management in Lebak Regency, West Java. Furthermore, the implication of this community service is to increase literacy and awareness among government officials about adequate waste management so that they can manage waste in their areas to reduce the negative impact of landfills.